How does Experiential Marketing Influence Consumer Behaviour? - Davey, Andrew William (Curtin University, 2025)
Experiential marketing (XM) has seen a rapid rise to prominence over the last two decades, however, research suggests that XM is still poorly understood by both academics and practitioners. The present thesis presents a much-needed conceptualisation of XM which is then tested and validated through two rounds of experimentally designed research. The resulting conceptual model significantly extends the conceptual and empirical understanding of XM for both sides of the academic/practitioner dyad.